PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA PERIMBANGAN TERHADAP BELANJA PEMELIHARAAN PADA ANGGARAN PEMERINTAH DAERAH - Aulia Fikki (IAIN Lhokseumawe, 2021)
This research is aimed to provide empirical evidence of the influence of real regional income (PAD) and proportion funding toward expense of maintenance through capital expenditure in Aceh government regency/ city and town from 2015 to 2017. Populations used in this research are 18 regencies, and 5 city and town in Aceh government. Due to the consideration of the data availability, therefore the main targets of this study are 13 regencies and 5 cities and town. The data analysis method used in this research is path analysis method.Result of the research shows that simultaneously the allocation of real regional income (PAD) and proportion funding are influential to capital expenditure and expense of maintenance. But, partially, real regional income (PAD) has a negative influence to the expense of maintenance, whereas proportion funding and capital expenditure partially influential toward expense of maintenance.